2019
DOI: 10.1080/02670836.2018.1549303
|View full text |Cite
|
Sign up to set email alerts
|

Development of 3rd generation Medium Mn duplex steels for automotive applications

Abstract: The mechanical behaviour and fracture were studied in a Fe–5Mn–2.5Al–0.2C (in wt-%) Medium Mn steel. Metallographic and magnetic measurements confirm the significant influence of the transformation kinetics of the strain-induced martensite on the mechanical properties and strain heterogeneities (Lüders and Portevin-Le Chatelier-like phenomena). An accurate study of isothermal evolutions of the microstructure, associated with atomistic calculations, complements current thermodynamic databases to quantify the na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Figure 36 shows the M(H) curves for a high-Mn steel cold rolled to several logarithmic strains (e), as reported in our preceding work [403] and provide us important parameters, such as the saturation magnetization (M s ) and the coercive field (H c ). The M s values mirror the volume fraction of ferromagnetic phases present in the specimen and thus they have extensively been used for tracking phase transformations in TRIP-assisted, [62,402] medium-Mn, [404,405] and high-Mn steels. [403,406,407] Figure 36, as an example, reveals the increase of the M s values as a function of plastic deformation, thus revealing the formation of strain-induced a¢-martensite upon rolling as confirmed by the EBSD maps displayed in Figure 36(b).…”
Section: E Magnetic Characterization Of Advanced High-strength Steelmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 36 shows the M(H) curves for a high-Mn steel cold rolled to several logarithmic strains (e), as reported in our preceding work [403] and provide us important parameters, such as the saturation magnetization (M s ) and the coercive field (H c ). The M s values mirror the volume fraction of ferromagnetic phases present in the specimen and thus they have extensively been used for tracking phase transformations in TRIP-assisted, [62,402] medium-Mn, [404,405] and high-Mn steels. [403,406,407] Figure 36, as an example, reveals the increase of the M s values as a function of plastic deformation, thus revealing the formation of strain-induced a¢-martensite upon rolling as confirmed by the EBSD maps displayed in Figure 36(b).…”
Section: E Magnetic Characterization Of Advanced High-strength Steelmentioning
confidence: 99%
“…Medium-Mn steels are generally composed of ferrite and metastable austenite which may undergo martensitic transformation upon straining. Perlade et al [404] tracked the evolution of the austenite fraction during tensile testing of a 5Mn-2.47Al-0.208C (wt pct) steel that was intercritically annealed at various temperatures (T IA = 740°C, 760°C, 780°C), Figure 38. They observed that the rate of the martensitic transformation increased with increasing T IA for the investigated steel.…”
Section: Magnetic Characterization Of Medium-mn Steelsmentioning
confidence: 99%
“…The impedance coil responds to the change in AC permeability of the specimen as its ferromagnetic content, that is, martensite content increases. Two methods are used to measure the permeability change, 1) by voltage measurement (transformer method) [112][113][114] or 2) by frequency measurement (resonant circuit method). [47,73,74,115,116] In the transformer technique, the magnitude of the phase of the induced AC voltage is measured in the sensing coil (that surrounds the specimen) as the secondary winding of a transformer for a known AC reference voltage.…”
Section: Design Of Ac Magnetic Permeability Test Set Upmentioning
confidence: 99%
“…[47] AC magnetic permeability Does not require extra sample preparation. [110][111][112][113][114][115][116][117] www.advancedsciencenews.com…”
Section: Ebsd Accuratementioning
confidence: 99%
“…For instance, with a reduced heating temperature, it is not possible to achieve high strength with thinner components; while with a reduced forming temperature only, thick oxidation and decarburisation layers cannot be avoided and the ductility is still not high enough to widen application in the automotive industry. Therefore, in recent years, attention has been focused on improving the steel grades to overcome these issues [80].…”
Section: Low-temperature Hot Stampingmentioning
confidence: 99%